2023
DOI: 10.3389/fnagi.2022.1045910
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cerebral small vessel diseases markers and cognitive performance in stroke-free patients with atrial fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is related to an increased risk of cognitive dysfunction. Besides clinically overt stroke, AF can damage the brain via several pathophysiological mechanisms. We aimed to assess the potential mediating role of cerebral small vessel disease (SVD) and cognitive performance in individuals with AF.MethodsStroke-free individuals with AF from the cardiological outpatient clinic at West China Hospital of Sichuan University were recruited. Extensive neuropsychological testing tools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…First, the sample size was small. Second, some aspects, such as delayed recall of the AVLTh, were not chosen in the present study, because patients with WMH were previously found to not show deficits in this domain[ 30 ]. In addition, 3T-WMH volume should be used to quantify WMH in future research.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size was small. Second, some aspects, such as delayed recall of the AVLTh, were not chosen in the present study, because patients with WMH were previously found to not show deficits in this domain[ 30 ]. In addition, 3T-WMH volume should be used to quantify WMH in future research.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, atrial brillation may signi cantly increase the risk of stroke, an important risk factor for cognitive dysfunction. On the other hand, even in the absence of stroke, asymptomatic cerebral infarction [20], unidenti able microinfarcts [21], and white matter hyperintensity [22] linked to atrial brillation are also very likely to result in cognitive decline and dementia such as Alzheimer's disease, and the related pathogeneses are still being con rmed and investigated. Standardized treatment [23] of atrial brillation and anticoagulation management [24,25] may have a speci c effect on delaying cognitive decline in patients.…”
Section: Introductionmentioning
confidence: 99%
“…listed the top ten authors related to AF and cognitive dysfunction, all of whom had published no less than 15 articles. Lip GYH (University of Liverpool, England) (48) is the most proli c author, followed by Gottesman RF (Johns Hopkins University, USA)(24), Mcmanus DD (University of Massachusetts, USA)(22), Alonso A (Emory University, USA) (20), Bunch TJ (University of Utah, USA)(20). Eight of the top ten authors were from the United States, the other two came from the UK and South Korea, and all belonged to different organizations.…”
mentioning
confidence: 99%